The president's daughter [large type] : a thriller - Clinton, Bill, 1946-; Patterson, James, 1947- (Little, Brown and Company, Alfred A. Knopf, 2021)
A one-time Navy SEAL and past president Matthew Keating, after his daughter is kidnapped by a madman, embarks on a one-man special-ops mission that tests his strengths as a leader, a warrior, and a father.